EEFECT OF DURATION OF USE OF HORMONAL CONTRACEPTIVE PILLS ON TOTAL LIPID AND LIPOPROTEINS IN NIGERIAN WOMEN. - EMOKPAE, MA; UADIA, PO; OSADOLOR, HB (International Journal of Pharma and Bio Sciences, 2010)
The study seeks to determine the effect of duration of oral contraceptive use on lipid and lipoproteins in Nigerian women. The study group was made of 120 women (mean age 24.1±5 years) who were on biphasic lofeminal tablets for a period ranging from 1- 48 months, while 50 age matched women with regular menstruation with no history of hormonal use within the last six months before the investigation were used as controls. Total lipid, triglyceride, total cholesterol, LDL-cholesterol and HDL-cholesterol were determined using standard colorimetric techniques. Statistically significant increases were observed for triglyceride, LDL-cholesterol, and VLDL cholesterol with the duration of oral contraceptive use. The level of total lipid did not increase beyond 24months of oral contraceptive intake while the level of HDL cholesterol was significantly decreased (p<0.05) with the duration of use. The atherogenic index of serum lipid declined with duration of oral contraceptive use and thus hormonal induced dyslipidaemia may not be regarded as proatherogenic . The study suggests that Oral contraceptive pills may not necessarily lead to pathologic concentration of lipid within 4 years duration of use in Nigerian women.